1981
DOI: 10.1136/jcp.34.3.314
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies to detect human tumours: an experimental approach.

Abstract: SUmmARY The use of monoclonal antibodies which can be raised to antigens of choice offers a selective and specific approach for the detection of tumours both in vivo and at a cellular level in biopsy specimens. We demonstrate that a monoclonal antibody raised to human teratoma will localise in a teratoma, growing as a xenograft in immune-suppressed mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…Mouse organs such as liver and spleen were used as negative controls, and no ARG evidence of antibody was found. It is of interest that other workers (Moshakis et al, 1981b) antibodies gives clearer results than conlabel has been found for ventional polyclonal antisera. The adys.…”
Section: Resultsmentioning
confidence: 99%
“…Mouse organs such as liver and spleen were used as negative controls, and no ARG evidence of antibody was found. It is of interest that other workers (Moshakis et al, 1981b) antibodies gives clearer results than conlabel has been found for ventional polyclonal antisera. The adys.…”
Section: Resultsmentioning
confidence: 99%
“…Large batches of antibody can be produced allowing the comparison of each preparation by different investigators. Labelled mouse monoclonal antibodies have been successfully used to localise tumour deposits in immuno-suppressed mice bearing human tumour xeongrafts (Levine et al, 1980;Moshakis et al, 1981). There are, however, few reports of the use of monoclonal antibodies for localisation of tumours in patients where the problems of cross reaction are completely different (Mach et al, 1981;Epenetos et al, 1982).…”
mentioning
confidence: 99%
“…In relation to this, we have shown by autoradiography that monoclonal antibodies raised to cell-surface antigens of human teratoma xenografts localize in close association to viable tumour cells after in vivo administration of the antibodies (Moshakis et al, 1981).…”
Section: Discussionmentioning
confidence: 88%
“…Experiments have started using affinitypurified antibodies to the epithelial membrane antigen (EMA) expressed by human breast carcinomas (Heyderman et al, 1979;Sloane & Ormerod, 1981) and to teratomas, through the use of monoclonal antibodies (Moshakis et al, 1981). We hope that this latter approach can, in time, be extended to the study of human breast carcinomas.…”
Section: Discussionmentioning
confidence: 99%